Dietary Strategies in Autism Spectrum Disorder (ASD) - Tas, Ayten Aylin (Progress in Nutrition, 2018)
Many children with Autism Spectrum Disorders (ASDs) have been reported to suffer from conditions (i.e. gastrointestinal distress, abnormal sensory processing, etc.) that may interfere with their nourishment. To compensate for possible deficiencies stemming from food selectivity and idiosyncratic eating habits and to alleviate some of the symptoms of ASD, a number of dietary strategies have been implemented by caregivers. Such strategies may include supplementation of diets with probiotics, omega-3 fatty acids, antioxidants, vitamins and minerals. Exclusion of certain nutrients from the diet (such as gluten, casein, carbohydrates, etc.) has also been resorted to. There are a vast number of studies conducted on dietary interventions in children with ASD, however, the results of these studies are confusing and inconclusive. This paper aims to critically review scientific studies on dietary strategies as applied to children with ASD and deduce practical implications from existing researches.